The descent of man and selection in relation to sex - Darwin, Charles 1809-1882 (Cambridge University Press, 2010)
In his introduction, Darwin reveals that for many years he had no intention of publishing his notes on this topic, 'as I thought that I should thus only add to the prejudices against my views'. By 1871, he felt that his fellow scientists would show a greater openness of mind to his arguments, even when taken to their logical conclusion and applied to the descent of man from the apes - the aspect of his theory which had been so widely mocked since the notorious question asked by Bishop Wilberforce at the Oxford debate of 1860: was it through his grandmother or his grandfather that Thomas Huxley, Darwin's champion, considered himself descended from a monkey? However, the book's focus on the area of sexual selection and the evolutionary importance of secondary sexual characteristics across the animal kingdom meant that the book was received without the public outrage that Darwin had feared.